Influence of technological usage on customer service and customer satisfaction in the banking sector - Francis Adanlawo, Eyitayo; Collins Owolabi, Oluwafemi; Yolanda Nkomo, Nomusa (Edelweiss Applied Science and Technology, 2024)
Technology-based self-service banking enables customers to complete services for themselves without support from bank staff. The study investigated the influence of technological usage on customer service and customer satisfaction in the Nigeria banking sector in Nigeria. The study made use of two objectives, which specifically find out the influence of technological usage on customer services and the influence of technological usage on customers’ satisfaction. Two null hypotheses were formulated to guide the study. A survey research design was adopted. The population of the study were commercial bank customers in Ondo State, Nigeria. A purposeful sampling technique was used to select one hundred participants from ten commercial banks in Ondo State. Results of the study reveal that technological usage has a significant influence on customer service [F (l, 98) 194.244; there is a significant influence of technological usage on customers’ satisfaction [F (1, 99) = 27.452; p<0.05]. It was concluded that the use of technologies in customers’ services can be used to increase the efficiency of banks.